2006
DOI: 10.1088/0963-0252/16/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Surface acid chemistry associated with dielectric barrier discharge (DBD) treatment of polyethylene

Abstract: The chemistry associated with atmospheric dielectric barrier discharges (DBDs) in air has been studied. Laboratory and industrial DBD systems have been investigated. In this work, we have emphasized the use of aqueous extractions of treated surfaces, followed by analyses by ion chromatography to study the DBD chemistry. A range of DBD factors including dose, humidity, airflow and electrode configuration (one versus two dielectric barriers) is found to influence the levels of acids, notably nitrous, nitric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The acidic effect was first evidenced and carefully studied by Moussa et al, , because of its key importance in the control of almost all the organic oxidation−reduction reactions . The study was extensively completed with the behavior of efficient acidity buffers, the pH of which decreased by 0.2 pH units only for 1 h of exposure to the discharge, which enables one to achieve many plasma treatments at stabilized pH.…”
Section: The Chemical Effects Of the Species Formed In The Discharge ...mentioning
confidence: 99%
See 4 more Smart Citations
“…The acidic effect was first evidenced and carefully studied by Moussa et al, , because of its key importance in the control of almost all the organic oxidation−reduction reactions . The study was extensively completed with the behavior of efficient acidity buffers, the pH of which decreased by 0.2 pH units only for 1 h of exposure to the discharge, which enables one to achieve many plasma treatments at stabilized pH.…”
Section: The Chemical Effects Of the Species Formed In The Discharge ...mentioning
confidence: 99%
“…It is well-known now that the acidity of an aqueous target exposed to an electric discharge in air increases (pH decreases) and that matching ions (i.e., mainly NO 2 − and NO 3 − ) enter the liquid phase, so that they induce an enhanced conductivity of the solution. The formation of nitrous/nitric acids is not limited to the treatment of solutions, because a DBD treatment of polyethylene in humid air reports indicates their presence. Those authors suggested the occurrence of an equilibrium.…”
Section: Post-discharge Reactionsmentioning
confidence: 99%
See 3 more Smart Citations